Structure for reducing electrocorrosion of stator winding outlet notch and forming method thereof
By using a combined semiconductor pad, felt assembly and conductive filling putty layer to fill the small gap in the outlet notch area of the air-cooled motor stator winding, a isopotential structure is formed, and the problem of electrical corrosion in the outlet notch area of the traditional motor stator winding is solved and the insulation operation safety of the motor is improved.
Patent Information
- Application Number
- CN202410678647.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-29
- Publication Date
- 2025-04-08
AI Technical Summary
There is an electrical corrosion problem in the outlet notch area of the stator winding of traditional air-cooled motors, mainly due to the small gap between the stator coil and the notch pad, which leads to potential difference causing discharge and electrical corrosion.
The combined semiconductor pad is used to contact the surface of the stator coil, and a small gap is filled with felt components and the conductive filling putty layer to form an equipotential structure to reduce the occurrence of discharge phenomena.
Effectively eliminate the small gap between the pads in the outlet notch area of the stator winding and the coil surface, reduce the risk of electric corrosion, and improve the safety, stability and reliability of motor insulation operation.
Smart Images

Figure CN119787695A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of the electrical industry, and particularly relates to a structure for reducing electrical corrosion of a stator winding slot and a forming method thereof. Background Art
[0002] The stator winding slot area of the high-voltage motor has a high potential, complex electric field distribution and concentrated thermal stress. The stator winding end leakage current and capacitive current are collected in the low-resistance anti-corona layer in the stator winding slot area, and then flow through the stator core to the grounding component. As the rated voltage level of the unit increases, the leakage current and capacitive current generated at the stator winding end also increase, and the heat loss generated in the stator winding slot area also increases significantly. In a humid environment and high-voltage operating conditions, the nitrate generated by the reaction with water vapor in the air further corrodes the low-resistance anti-corona layer in the slot area.
[0003] At the same time, during the installation process, the stator coil hoisting area is at the slot, which is easy to wear the low-resistance anti-corona layer in the slot area; in order to increase the mechanical strength of the stator winding end support, after the stator coil is embedded in the circumferentially distributed stator core slots, a slot pad is installed in the stator winding slot area, and the conformable felt is impregnated with room temperature curing epoxy glue. The impregnated conformable felt wrapped pad is used to stuff the gap between the slot areas of two adjacent coils. Due to the differences in the stator core diameter and the number of core slots, there is a deviation of 0.5mm to 3mm in the spacing between the upper and lower sides of adjacent coils. The slot fixing structure of the conformable felt wrapped pad cannot completely fill the spacing deviation between adjacent coils. There is a small gap of 0.3mm to 1mm between the pad and the coil slot. The existing potential difference can easily cause discharge and produce electrical corrosion, especially for air-cooled motors with a rated voltage of 18kV and above. For air-cooled units with severe operating conditions such as frequent start-stop or peak-shaving and frequency regulation, the fixed structure in the stator winding slot area may creep and loosen with long-term operation of the unit. Small gaps in the slot area may also cause discharge and produce electrical corrosion. Summary of the invention
[0004] In order to solve the electro-corrosion phenomenon caused by the conventional air-cooled motor stator winding slot pad fixing structure, a structure for reducing the electro-corrosion of the stator winding slot and a forming method thereof are provided, which effectively eliminates the small gap between the pad in the stator winding slot area and the stator coil surface, forms an equipotential between the combined semiconductor pad and the stator coil surface, reduces the probability of electro-corrosion of the stator winding slot, and improves the safety, stability and reliability of the motor insulation operation.
[0005] The objective of the present invention is achieved through the following technical solutions: A structure for reducing electrical corrosion at a stator winding slot includes a stator coil, a combined semiconductor pad is arranged between two stator coils, a felt assembly and a conductive filling putty layer are arranged between the stator coil and the combined semiconductor pad, the felt assembly is arranged close to the stator coil, and the conductive filling putty layer is arranged close to the combined semiconductor pad.
[0006] Preferably, the combined semiconductor pad includes two wedge-shaped pads, and the two wedge-shaped pads are fixed by a binding belt.
[0007] Preferably, the combined semiconductor pad includes two wedge-shaped pads and a square pad, the two wedge-shaped pads and the square pad are fixed by a binding belt, and the square pad is arranged between the two wedge-shaped pads.
[0008] A forming method of a structure for reducing electrical corrosion of a stator winding slot, comprising the following steps: after the stator coil is embedded in the core slot, the insulating surface of the stator coil slot area is cleaned with white cotton cloth dipped in an appropriate amount of anhydrous alcohol, a modular semiconductor pad is wrapped with a felt component impregnated with a two-component low-resistance anti-corona paint, and the pad is slowly inserted into the gap between two adjacent stator coils, and an insulating plate is knocked with a rubber hammer to make the modular semiconductor pad and the surface of the stator coil fit and flat; nano-conductive filling putty is used to inject and fill the small gap and uneven area between the modular semiconductor pad and the surface of the stator coil, and a small round polytetrafluoroethylene rod is used to smooth the injection area; and the modular semiconductor pad is continuously tied and fixed with a binding tape impregnated with a room temperature curing epoxy adhesive with a high glass transition temperature, and cured at room temperature for not less than 48 hours.
[0009] Preferably, the combined semiconductor pad adopts a high-strength semiconductor laminated glass cloth board, the tensile strength of the high-strength semiconductor laminated glass cloth board is greater than 250MPa, the vertical layer bending strength of the high-strength semiconductor laminated glass cloth board is greater than 400MPa, and the surface resistivity of the high-strength semiconductor laminated glass cloth board is 1kΩ~50kΩ.
[0010] Preferably, the two-component low-resistance anti-corona paint includes component A and curing agent B, the weight ratio of component A to curing agent B is 10:1, the component A includes epoxy-based paint and graphite filler, the solid content of the two-component low-resistance anti-corona paint is greater than 55%, the viscosity of the two-component low-resistance anti-corona paint at 23° C. is 40s to 80s, and the surface resistivity of the two-component low-resistance anti-corona paint is 0.5kΩ to 8kΩ.
[0011] Preferably, the nano conductive filled putty includes component A and curing agent B, the weight ratio of component A to curing agent B is 10:1, the component A includes epoxy paint and nano conductive filler, the solid content of the nano conductive filled putty is greater than 70%, and the surface resistivity of the nano conductive filled putty is 20kΩ~100kΩ.
[0012] Preferably, the room temperature curing epoxy adhesive with a high glass transition temperature comprises a low viscosity epoxy resin and an amine curing agent, the weight ratio of the low viscosity epoxy resin to the amine curing agent is 100:22-28, the solid content of the room temperature curing epoxy adhesive with a high glass transition temperature is greater than 98%, the viscosity of the room temperature curing epoxy adhesive with a high glass transition temperature at 23°C is 300mPa.s-600mPa.s, the glass transition temperature of the room temperature curing epoxy adhesive with a high glass transition temperature is greater than 85°C, and the relative tracking resistance index CTI of the room temperature curing epoxy adhesive with a high glass transition temperature is greater than 600V.
[0013] Preferably, the width of the felt assembly is 1 mm to 2 mm greater than the width of the combined semiconductor pad, and the length of the felt assembly is 2 mm to 4 mm greater than the length of the combined semiconductor pad.
[0014] Preferably, the felt component is needle-punched polyester, which is impregnated with room-temperature curing epoxy glue with a high glass transition temperature. After the needle-punched polyester felt is soaked, excess glue on the surface is twisted off, and the felt is left at room temperature for 2 to 4 hours to reach a semi-cured state; the needle-punched polyester that has been dried to a semi-cured state is impregnated with two-component low-resistance anti-corona paint, and after the needle-punched polyester is soaked, excess two-component low-resistance anti-corona paint on the surface is twisted off.
[0015] The beneficial effects of this technical solution are as follows: 1. The present invention provides a structure for reducing electrical corrosion at the slot of the stator winding. The combined semiconductor pad has a larger and more fitted contact area with the coil surface, reducing the small gap between the pad and the coil surface. At the same time, the combined semiconductor slot pad is made of semiconductor material, which is close to the resistivity of the low-resistance anti-corona layer on the coil surface, forming an equipotential structure and reducing the occurrence of small gap discharge.
[0016] 2. The present invention provides a structure for reducing the electro-corrosion of the stator winding slot. The conventional stator winding slot area is tied and fixed using an integral insulating pad wrapped with a felt impregnated with ordinary epoxy glue. The insulation resistance of the felt after impregnation is greater than 10 14 Ω, when there is a small gap between the stator coil and the slot pad, a potential difference of several volts can easily cause discharge and damage the low-resistance anti-corona layer; the low-resistance anti-corona paint using a two-component epoxy paint base in the present invention has a high solid content, stable resistivity, and strong current carrying capacity. The surface resistivity of the felt after being impregnated with the two-component low-resistance anti-corona paint is close to the resistivity of the low-resistance anti-corona layer on the surface of the stator coil, which is less than 10 5 Ω, further ensuring the equipotential structure of the combined semiconductor pad, felt assembly and stator coil surface, and further reducing the occurrence of small gap discharge.
[0017] 3. The present invention provides a structure for reducing electrical corrosion at the slot outlet of the stator winding. The stator winding slot outlet fixing structure forms effective electrical contact with the low-resistance anti-corona layer of the stator coil, ensuring the smooth flow of current, improving the anti-corona performance of the stator winding slot outlet area, and effectively increasing the anti-corona service life of the stator coil and winding.
[0018] 4. The present invention provides a molding method for a structure for reducing electrical corrosion at the slot of a stator winding. Nano-conductive filling putty is used to inject and fill the small gaps and uneven areas between the slot pad and the coil surface, effectively reducing the small gaps between the combined semiconductor pad and the surface of the stator coil. The epoxy nano-conductive putty forms a conductive channel with a small gap, further reducing the occurrence of electrical corrosion at the slot of the stator winding. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a structural schematic diagram of the motor stator in the present invention; Figure 2 yes Figure 1 Sectional view of AA in the middle; Among them: 1. stator coil; 2. combined semiconductor pad; 3. felt assembly; 4. conductive filling putty layer. DETAILED DESCRIPTION
[0020] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0021] Example 1 like Figure 1-Figure 2 As shown, a structure for reducing electrical corrosion at the slot of a stator winding includes a stator coil 1, a combined semiconductor pad 2 is arranged between two electronic coils, a felt assembly 3 and a conductive filling putty layer 4 are arranged between the stator coil 1 and the combined semiconductor pad 2, the felt assembly 3 is arranged close to the stator coil 1, and the conductive filling putty layer 4 is arranged close to the combined semiconductor pad 2.
[0022] Example 2 The difference between this embodiment and embodiment 1 is that the combined semiconductor pad 2 includes two wedge-shaped pads, which are fixed by a binding belt. An opening is provided in the middle area of the wedge-shaped pad, and the binding belt passes through the opening to fix the two wedge-shaped pads.
[0023] Example 3 The difference between this embodiment and embodiment 1 is that the combined semiconductor pad 2 includes two wedge-shaped pads and a square pad, the two wedge-shaped pads and the square pad are fixed by a binding belt, and the square pad is arranged between the two wedge-shaped pads. An opening is arranged in the middle area of the two wedge-shaped pads and the square pad, and the binding belt passes through the opening to fix the two wedge-shaped pads and the square pad.
[0024] Example 4 A structure for reducing electrical corrosion at the slot of a stator winding in Examples 1 to 3, and a forming method thereof, comprising the following steps: after the stator coil 1 is embedded in the core slot, use white cotton cloth dipped in an appropriate amount of anhydrous alcohol to clean the insulating surface of the slot area of the stator coil 1, wrap the modular semiconductor pad 2 with a felt component 3 impregnated with a two-component low-resistance anti-corona paint, slowly insert it into the gap between two adjacent stator coils 1, and use a rubber hammer to knock on the insulating plate to make the modular semiconductor pad 2 and the surface of the stator coil 1 fit and flat; use nano-conductive filling putty to inject and fill the small gap and uneven area between the modular semiconductor pad 2 and the surface of the stator coil 1, and use a small round polytetrafluoroethylene rod to smooth the injection area; use a binding tape impregnated with room temperature curing epoxy glue with a high glass transition temperature to continuously bind and fix the modular semiconductor pad 2, and cure it at room temperature for not less than 48 hours.
[0025] Among them, the combined semiconductor pad 2 adopts a high-strength semiconductor laminated glass cloth board, the tensile strength of the high-strength semiconductor laminated glass cloth board is greater than 250MPa, the vertical layer bending strength of the high-strength semiconductor laminated glass cloth board is greater than 400MPa, and the surface resistivity of the high-strength semiconductor laminated glass cloth board is 1kΩ~50kΩ.
[0026] Among them, the two-component low-resistance anti-corona paint includes component A and curing agent B, the weight ratio of component A to curing agent B is 10:1, the component A includes epoxy-based paint and graphite filler, the curing agent B adopts an amine curing agent, the solid content of the two-component low-resistance anti-corona paint is greater than 55%, the viscosity of the two-component low-resistance anti-corona paint at 23°C is 40s~80s, and the surface resistivity of the two-component low-resistance anti-corona paint is 0.5kΩ~8kΩ.
[0027] Among them, the nano conductive filled putty includes component A and curing agent B, the weight ratio of component A to curing agent B is 10:1, the component A includes epoxy paint and nano conductive filler, the curing agent B adopts amine curing agent, the solid content of the nano conductive filled putty is greater than 70%, and the surface resistivity of the nano conductive filled putty is 20kΩ~100kΩ.
[0028] Among them, the room-temperature curing epoxy adhesive with high glass transition temperature includes a low-viscosity epoxy resin and an amine curing agent, the weight ratio of the low-viscosity epoxy resin to the amine curing agent is 100:22-28, the solid content of the room-temperature curing epoxy adhesive with high glass transition temperature is greater than 98%, the viscosity of the room-temperature curing epoxy adhesive with high glass transition temperature at 23°C is 300mPa.s-600mPa.s, the glass transition temperature of the room-temperature curing epoxy adhesive with high glass transition temperature is greater than 85°C, and the relative tracking resistance index CTI of the room-temperature curing epoxy adhesive with high glass transition temperature is greater than 600V.
[0029] The width of the felt component 3 is 1 mm to 2 mm greater than the width of the combined semiconductor pad 2 , and the length of the felt component 3 is 2 mm to 4 mm greater than the length of the combined semiconductor pad 2 .
[0030] Among them, the felt component 3 is needle-punched polyester, which is impregnated with room-temperature curing epoxy glue with a high glass transition temperature. After the needle-punched polyester felt is soaked, excess glue on the surface is twisted off and left at room temperature for 2h to 4h to a semi-cured state; the needle-punched polyester that has been dried to a semi-cured state is impregnated with two-component low-resistance anti-corona paint, and after the needle-punched polyester is soaked, excess two-component low-resistance anti-corona paint on the surface is twisted off.
[0031] The beneficial effects of this technical solution are as follows: 1. The present invention provides a structure for reducing electrical corrosion at the slot of the stator winding. The combined semiconductor pad 2 has a larger contact area with the coil surface and is more fitted, reducing the small gap between the pad and the coil surface. At the same time, the combined semiconductor slot pad is made of semiconductor material, which is close to the resistivity of the low-resistance anti-corona layer on the coil surface, forming an equipotential structure and reducing the occurrence of small gap discharge.
[0032] 2. The present invention provides a structure for reducing the electro-corrosion of the stator winding slot. The conventional stator winding slot area is tied and fixed using an integral insulating pad wrapped with a felt impregnated with ordinary epoxy glue. The insulation resistance of the felt after impregnation is greater than 10 14 Ω, when there is a small gap between the stator coil 1 and the slotted pad, a potential difference of several volts can easily cause discharge and damage the low-resistance anti-corona layer; the low-resistance anti-corona paint based on a two-component epoxy paint used in the present invention has a high solid content, stable resistivity, and strong current carrying capacity. The surface resistivity of the felt impregnated with the two-component low-resistance anti-corona paint is close to the resistivity of the low-resistance anti-corona layer on the surface of the stator coil 1, which is less than 10 5 Ω, further ensuring the equipotential structure of the combined semiconductor pad 2, the felt assembly 3 and the surface of the stator coil 1, and further reducing the occurrence of small gap discharge.
[0033] 3. The present invention provides a structure for reducing electrical corrosion at the slot outlet of the stator winding. The stator winding slot outlet fixing structure forms effective electrical contact with the low-resistance anti-corona layer of the stator coil 1, ensuring the smooth flow of current, improving the anti-corona performance of the stator winding slot outlet area, and effectively increasing the anti-corona service life of the stator coil 1 and the winding.
[0034] 4. The present invention provides a molding method for a structure for reducing electrical corrosion at the slot of a stator winding. Nano-conductive filling putty is used to inject and fill the small gap and uneven area between the slot pad and the coil surface, effectively reducing the small gap between the combined semiconductor pad 2 and the surface of the stator coil 1. The epoxy nano-conductive putty forms a conductive channel with a small gap, further reducing the occurrence of electrical corrosion at the slot of the stator winding.
[0035] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification or equivalent change made to the above embodiment based on the technical essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A structure for reducing electrical corrosion of stator winding slots, characterized in that: It includes a stator coil, a combined semiconductor pad is arranged between two stator coils, a felt component and a conductive filling putty layer are arranged between the stator coil and the combined semiconductor pad, the felt component is arranged close to the stator coil, and the conductive filling putty layer is arranged close to the combined semiconductor pad.
2. The structure for reducing stator winding slot electrical corrosion according to claim 1, characterized in that: The combined semiconductor pad includes two wedge-shaped pads, which are fixed by a binding belt.
3. The structure for reducing stator winding slot electrical corrosion according to claim 1, characterized in that: The combined semiconductor pad comprises two wedge-shaped pads and a square pad, the two wedge-shaped pads and the square pad are fixed by a binding belt, and the square pad is arranged between the two wedge-shaped pads.
4. A method for forming a structure for reducing electrical corrosion of stator winding slots, characterized in that: The following steps are involved: After the stator coil is embedded in the core slot, use white cotton cloth dipped in an appropriate amount of anhydrous alcohol to clean the insulating surface of the stator coil slot area, wrap the modular semiconductor pad with a felt assembly impregnated with a two-component low-resistance anti-corona paint, and slowly insert it into the gap between the two adjacent stator coils. Use a rubber hammer to knock on the insulating plate to make the modular semiconductor pad and the stator coil surface fit and flat; use nano-conductive filling putty to inject and fill the small gaps and uneven areas between the modular semiconductor pad and the stator coil surface, and use a small polytetrafluoroethylene round rod to smooth the injection area; use a binding tape impregnated with room-temperature curing epoxy glue with a high glass transition temperature to continuously bind and fix the modular semiconductor pad, and cure it at room temperature for not less than 48 hours.
5. The method for forming a structure for reducing electro-corrosion of stator winding slots according to claim 4, characterized in that: The combined semiconductor pad adopts a high-strength semiconductor laminated glass cloth plate, the tensile strength of the high-strength semiconductor laminated glass cloth plate is greater than 250MPa, the vertical layer bending strength of the high-strength semiconductor laminated glass cloth plate is greater than 400MPa, and the surface resistivity of the high-strength semiconductor laminated glass cloth plate is 1kΩ to 50kΩ.
6. The method for forming a structure for reducing electro-corrosion of stator winding slots according to claim 4, characterized in that: The two-component low-resistance anti-corona paint includes component A and curing agent B, the weight ratio of component A to curing agent B is 10:1, the component A includes epoxy-based paint and graphite filler, the solid content of the two-component low-resistance anti-corona paint is greater than 55%, the viscosity of the two-component low-resistance anti-corona paint at 23° C. is 40s to 80s, and the surface resistivity of the two-component low-resistance anti-corona paint is 0.5kΩ to 8kΩ.
7. The method for forming a structure for reducing electro-corrosion of stator winding slots according to claim 4, characterized in that: The nano conductive filled putty includes component A and curing agent B, the weight ratio of component A to curing agent B is 10:1, the component A includes epoxy paint and nano conductive filler, the solid content of the nano conductive filled putty is greater than 70%, and the surface resistivity of the nano conductive filled putty is 20kΩ to 100kΩ.
8. The method for forming a structure for reducing electro-corrosion of stator winding slots according to claim 4, characterized in that: The room temperature curing epoxy adhesive with a high glass transition temperature includes a low viscosity epoxy resin and an amine curing agent, the weight ratio of the low viscosity epoxy resin to the amine curing agent is 100:22-28, the solid content of the room temperature curing epoxy adhesive with a high glass transition temperature is greater than 98%, the viscosity of the room temperature curing epoxy adhesive with a high glass transition temperature at 23°C is 300mPa.s-600mPa.s, the glass transition temperature of the room temperature curing epoxy adhesive with a high glass transition temperature is greater than 85°C, and the relative tracking resistance index CTI of the room temperature curing epoxy adhesive with a high glass transition temperature is greater than 600V.
9. The method for forming a structure for reducing electro-corrosion of stator winding slots according to claim 4, characterized in that: The width of the felt assembly is 1 mm to 2 mm greater than the width of the combined semiconductor pad, and the length of the felt assembly is 2 mm to 4 mm greater than the length of the combined semiconductor pad.
10. The method for forming a structure for reducing electro-corrosion of stator winding slots according to claim 4, characterized in that: The felt component is needle-punched polyester, which is impregnated with room-temperature curing epoxy glue with a high glass transition temperature. After the needle-punched polyester felt is soaked, excess glue on the surface is twisted off and the felt is left at room temperature for 2 hours to 4 hours until it reaches a semi-cured state; the needle-punched polyester that has been dried to a semi-cured state is impregnated with two-component low-resistance anti-corona paint, and after the needle-punched polyester is soaked, excess two-component low-resistance anti-corona paint on the surface is twisted off.